A Blockchain Protocol for Authenticating Space Communications between Satellites Constellations - Mohamed Torky; Tarek Gaber; Essam Goda; Vaclav Snasel; Aboul Ella Hassanien (Aerospace, 2022)
Blockchain has found many applications, apart from Bitcoin, in different fields and it has the potential to be very useful in the satellite communications and space industries. Decentralized and secure protocols for processing and manipulating space transactions of satellite swarms in the form of Space Digital Tokens (SDT) can be built using blockchain technology. Tokenizing space transactions using SDTs will open the door to different new blockchain-based solutions for the advancement of constellation-based satellite communications in the space industry. Developing blockchain solutions using smart contracts could be used in securely authenticating various P2P satellite communications and transactions within/between satellite swarms. To manage and secure these transactions, using the proposed SDT concept, this paper suggested a blockchain-based protocol called Proof of Space Transactions (PoST). This protocol was adopted to manage and authenticate the transactions of satellite constellations in a P2P connection. The PoST protocol was prototyped using the Ethereum blockchain and experimented with to evaluate its performance using four metrics: read latency, read throughput, transaction latency, and transaction throughput. The simulation results clarified the efficiency of the proposed PoST protocol in processing and verifying satellite transactions in a short time according to read and transaction latency results. Moreover, the security results showed that the proposed PoST protocol is secure and efficient in verifying satellite transactions according to true positive rate (TPR), true negative rate (TNR), and accuracy metrics. These findings may shape a real attempt to develop a new generation of Blockchain-based satellite constellation systems.